Investigating the Effects of Microwave Energy on Synthesis of Organic Compounds - Aminzai, Mohammad Tahir; Zhwand, Abdul Karim (Journal of Natural Sciences – Kabul University, 2024)
Microwave radiation is a kind of electromagnetic energy that has a frequency between 0.3 GHz and 300 GHz and a wavelength between 1 mm and 1 m. Microwave energy has grown in popularity as a heating technology in organic synthesis, mainly due to its increased reaction rate, lower energy consumption, higher yields, enhanced selectivity, ease of operation, and environmental friendliness. Since 1980, the usage of microwave reaction systems in chemistry as a strong, dependable energy source has expanded to include a wide range of processes, including dehydration, polymerization, extraction, synthesis of fine compounds, and organic synthesis. The influence of microwave radiation on reaction rates, yields, reaction times, and selectivity of particular types of organic reactions will be the main emphasis of this review paper.